The role of social support in improving self-confidence in adolescents who follow the organization of the qur'an rabbani companions - Taqiyah Anasa Irsyah; Zahro Varisna Rohmadani (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
Self-confidence is an individual's belief in their ability to perform tasks, characterized by confidence in their skills, optimism, objectivity, responsibility, rationality, and awareness of reality. One factor that can improve self-confidence is social support. Social support can help individuals feel more confident and capable of demonstrating their abilities. This study aims to investigate the role of social support in improving self-confidence among adolescents who are members of the Sahabat Qur’an Rabbani Organization. This study employed quantitative approach, specifically using correlational research methods. The subjects were adolescents aged 12-22 who are members of the Sahabat Qur’an Rabbani Organization. This study used purposive sampling techniques and collected data through a Likert scale, which was then analyzed using Pearson's product-moment correlation. The results showed a positive relationship between social support and increased self-confidence, with a significance level of p = 0.002 (p < 0.05) and a correlation coefficient of 0.430. This indicates that the two variables have a positive relationship, where social support can improve self-confidence in adolescents, and vice versa.